2014
DOI: 10.3109/10826084.2014.933240
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Substance Use Among Young Adults Transitioning Away from High School: A Narrative Review

Abstract: Twenty six studies were included in the review. The majority of the studies (19) examined substance use during the transition from high school to post-secondary settings. Seven studies examined substance use in post-secondary settings. The studies consistently found that substance use increases among young adults as they transition away from high school. During the transition away from high school, common predictors of substance use include substance use in high school, and peer influence. Common predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 59 publications
6
21
0
9
Order By: Relevance
“…First, the vast majority of the signs of the associations between predictors and outcomes are consistent with those in prior studies of military (Suris & Lind, 2008; Elbogen et al 2010; Turchik & Wilson, 2010; Nock et al 2013; Afifi et al 2016) and civilians (Dahlberg, 1998; Kilpatrick et al 2000; Kirst et al 2014; Rytila-Manninen et al 2014). The major exception is as that religiosity is positively associated with risk of sexual assault perpetration and positive drug tests.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…First, the vast majority of the signs of the associations between predictors and outcomes are consistent with those in prior studies of military (Suris & Lind, 2008; Elbogen et al 2010; Turchik & Wilson, 2010; Nock et al 2013; Afifi et al 2016) and civilians (Dahlberg, 1998; Kilpatrick et al 2000; Kirst et al 2014; Rytila-Manninen et al 2014). The major exception is as that religiosity is positively associated with risk of sexual assault perpetration and positive drug tests.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, we considered all potential predictors for which there was any evidence in the literature; e.g., risk-protective factors for suicidality (Nock et al 2013; Afifi et al 2016), mental hospitalization (Iribarren et al 2000; Rytila-Manninen et al 2014), substance problems (Kilpatrick et al 2000; Kirst et al 2014), TBI (Cassidy et al 2004; Elmasry et al 2017), other severe physical injuries (Bulzacchelli et al 2014; Theodoroff et al 2015) , violence perpetration (Dahlberg, 1998; Elbogen et al 2010), violence victimization (Suris & Lind, 2008; Turchik & Wilson, 2010), and career problems (Knapik et al 2004; Booth-Kewley et al 2010). In total, 727 independent variables were operationalized from the SAQ in addition to 8 performance-based neurocognitive test measures assessed in conjunction with the SAQ and 37 basic administrative variables recorded for all new soldiers at the beginning of service (772 total variables).…”
Section: Methodsmentioning
confidence: 99%
“…Although substance use began in adolescence, many participants in the study experienced more accepting attitudes and increased access to substances in college. These sentiments reflect findings of previous quantitative studies, which revealed that substance use increases as students transition out of high school (Kirst et al, ; White et al, ). Given the decrease in parental supervision, increase in unstructured time, easy access, and social norms related to drug and alcohol use, participants' reports of increased substance use in college are not surprising.…”
Section: Discussionsupporting
confidence: 87%
“…Second, the 3‐way interactions examined in this study do not reflect the full complexity of either genetic or environmental mechanisms in substance use. Future studies will also need to examine other environmental factors directly implicated in substance use in emerging adults, including parental rule setting, educational attainment, neighborhood characteristics, and peer influence . Third, our survey on tobacco and cannabis use was only limited to ascertain whether participants ever consumed any of these substances, but did not measure frequency and problematic patterns of use; future studies will be necessary to verify whether and how these aspects can be influenced by MAOA genotype.…”
Section: Discussionmentioning
confidence: 99%